The Expression of The P53 Gene Suppressor in Breast Cancer - B. B. Latipov; D. A. Nishanov; M. A. Gafur Akhunov; G. N. Saidov; M. T. Tukhtabayeva; A. B. Yigitaliev (Scientific Trends, 2024)
The article examines the indicators of the P53 gene suppressor in the Luminal type of breast cancer, and it has been established that the activity of tumor cells depends on the Luminal type. According to the results of the conducted study, the P53 index in Luminal A type of breast cancer had a high positive response in 10% of patients, while in Luminal B type (Her-2 negative), a high positive response was observed in 20% of patients. For luminol B (Her-2-positive), this indicator was 40%. In the basal-like (tripple negative) type, the high positive reaction of P53 was 60%. The Her-2 positive (non-luminal) type also showed a high positive response of 90%. As can be seen from the presented data, a high expression of the p53 gene suppressor is observed in luminal breast tumors, which are prognostically unfavourable. This, of course, should be taken into consideration when determining treatment tactics and studying the prognosis of breast cancer.
Keywords: Breast cancer, immunohistochemistry, gene suppressor, tumor Luminal type, prognosis, treatment tactics.